Development of a Kayak Race Prediction Including Environmental and Athlete Effects. (2016) - Higgens, Adam; Conway, Lauren; Banks, Joe; Taunton, Dominic; Hudson, Dominic; Turnock, Stephen
Abstract: The aim of this study is to produce a simulator for sprint kayak racing which would allow the prediction of race times based on the physiological capabilities and mass of a given athlete. The simulator has been verified using established empirical data for the prediction of environmental effects and has been shown to be accurate, however verification of the physiological model is difficult to do by using general race data. An investigation into the fatigue model which has been implemented shows that further investi- gation is required to calibrate the simulator and produce more accurate results over a variety of distances. However, the simulator does show quite how sensitive the selection of appropriate level of effort is to the final race time for the 1000m.